Fostering Interpersonal Intelligence in Early Childhood Through Traditional Gobak Sodor Game - Masudah, Nur Fairuz Faizatul; Sudaryanti (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
The golden age of early childhood is a crucial period for developing multiple intelligences, including interpersonal intelligence. Interpersonal intelligence refers to the ability to relate to and collaborate with others. This intelligence can be stimulated through traditional games, one of which is gobak sodor. This study employed a quantitative research approach with a descriptive design using correlational analysis. The objective was to examine the relationship between the traditional gobak sodor game and the interpersonal intelligence of children. The study population comprised all children aged 5–6 years, with a purposive sampling technique used to select 35 participants. Data collection methods included observation and documentation. The data were analyzed using simple correlational analysis through IBM SPSS Statistics version 26.0, preceded by a normality test. The results of the correlation test showed a significance value of 0.000 < 0.05, indicating a significant relationship. Furthermore, the Pearson correlation coefficient of 0.810 suggests a strong and positive correlation between the variables. These findings highlight that the traditional gobak sodor game is an effective medium for stimulating interpersonal intelligence in children. It underscores the importance of integrating traditional games into early childhood education to enhance social and collaborative skills, contributing to holistic development.